(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to identify and analyze questions from Arabic language books in preparatory vocational schools according to the modified Bloom’s taxonomy and reading comprehension skills. The research population consists of 526 questions, including 197 questions for the topics of the seventh-grade book, with a percentage of 37.5%, the eighth-grade book 190 questions, with a percentage of 36.1%, and the ninth-grade book 139 questions, with a percentage of 26.4%. The researcher prepared a list that includes criteria for good questions that measure modified Bloom’s taxonomy questions, reading comprehension skills, and the type of questions (essay and objective). It was presented to a group of experts in the Arabic language, methods of teaching the Arabic language, methods of teaching science, measurement, and evaluation, and the following criteria obtained complete agreement. Thus, it was adopted to become a valid tool. To achieve the research objectives, the researcher used chi-square, percentage, and HolsTi equations to analyze the collected data.